Professional Sports Trainers' Burnout in Fully Online and Blended Classes: Innovative Approaches in Physical Education and Sports Training - Nguyễn, Hoàng Minh Thuận; Ɖỗ, Thị Hoài Thu'; Nguyễn, Nhật Quang (Frontiers in Education, 2022)
The COVID-19 pandemic has forced many educational institutions worldwide to establish emergency remote teaching systems. Although online teaching has long been applied in many other subjects, online sports training is still under-researched in developing countries like Vietnam. In Vietnam, sports trainers are innovatively making many efforts to teach sports online amidst such a once-in-many-generations event. Particularly, a gym center chain has been offering two special formats of online courses utilizing virtual reality (VR) and three-dimensional (3D) technologies, namely, fully online and blended courses. The first format comprises 50% asynchronous sessions using VR and 3D technologies to provide trainees with theoretical knowledge and 50% offline sessions for practical skills training. The second format also includes 50% asynchronous sessions using the same technologies; however, the training for practical skills is conducted via an e-conferencing platform (Zoom). Fortunately, the blended courses have attracted significant attention from many sports trainees. However, as sports trainers in Vietnam had minimal opportunities to teach online before this epidemic, it is likely that, while teaching these courses, they can encounter moments of burnout, which comprises three dimensions, such as exhaustion, cynicism, and low professional efficacy. Thus, we aim to investigate factors that affected each dimension of burnout among sports trainers, using the mixed-method approach with questionnaires and focus-group interviews within this study. This study suggests practical pedagogical implications for sports trainers and administrators to curb stress and burnout in online sports training courses in times of crisis.